2010
DOI: 10.1213/ane.0b013e3181c76f52
|View full text |Cite
|
Sign up to set email alerts
|

The Direct Effect of Levobupivacaine in Isolated Rat Aorta Involves Lipoxygenase Pathway Activation and Endothelial Nitric Oxide Release

Abstract: Our data indicate that levobupivacaine-induced contraction of rat aortic smooth muscle is mediated mainly by activation of the lipoxygenase pathway and in part by activation of the cyclooxygenase pathway. In addition, activation of the lipoxygenase pathway seems to facilitate calcium influx via L-type calcium channels. Endothelial nitric oxide attenuates levobupivacaine-induced contraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
31
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 31 publications
5
31
0
Order By: Relevance
“…Levobupivacaine increases intracellular calcium concentration and intrinsically produces vasoconstriction in isolated vessels (Choi et al 2010). In addition, low doses of levobupivacaine produce vasoconstriction in human skin vessels in vivo because of its intrinsic vasoconstrictive properties (Newton et al 2000(Newton et al , 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Levobupivacaine increases intracellular calcium concentration and intrinsically produces vasoconstriction in isolated vessels (Choi et al 2010). In addition, low doses of levobupivacaine produce vasoconstriction in human skin vessels in vivo because of its intrinsic vasoconstrictive properties (Newton et al 2000(Newton et al , 2005.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was shown that the effect of LEVO on rat aorta was dependent on nitric oxide released by the endothelium 8 . These findings reinforce that the vascular effects of LEVO may differ depending on some variables, such as the vascular bed used.…”
Section: Discussionmentioning
confidence: 98%
“…Studies showed that LEVO in 50% enantiomeric excess induced certain intrinsic vasoconstriction in vitro [8][9][10]12,16 and in vivo [17][18][19] . Therefore, this study aimed to assess the vasoactivity of LEVO in in vitro experiments using arterial rings prepared from isolated rat superior mesenteric artery, a resistant artery, which can reflect the possible effects on the vascular reactivity in smaller blood vessels such as those present in the area treated by local anesthetic in clinical dentistry.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations